The distribution and occurrence of mosquito larvae (Diptera: Culicidae) in the Tongatapu Island Group, Kingdom of Tonga. Issue 2 (11th June 2016) - Swan, Tom; Harding, Jon
Abstract: The global expansion of air, sea and land transport networks has greatly enhanced the spread of mosquitoes internationally. In the Pacific, the incidence of mosquito‐borne diseases has been increasing in recent years. The Kingdom of Tonga has had numerous disease outbreaks from dengue fever and chikungunya viruses over recent years. Previous research has catalogued mosquito species occurrences and distributions throughout Tonga. However, it is unknown whether new species have arrived in Tonga, and if distribution of previously found species has changed since the last comprehensive survey in 2006. Consequently, we conducted a mosquito larval survey between November and December 2013 at 84 sites across four islands (Tongatapu, Pangaimotu, 'Oneata and 'Eua) in the Tongatapu Island Group to record the distribution and occurrence of mosquito larvae. Larvae were more frequently collected in artificial (e.g. abandoned car tyres, 55‐gallon plastic drums and plastic containers) than natural (e.g. pools, ponds and tree holes) habitats. Larvae of nine mosquito species were collected in the Tongatapu Island Group: Aedes aegypti, A. albopictus, A. tongae, A. horrescens, A. vexans nocturnus, Culex annulirostris, C. albinervis, C. quinquefasciatus and C. sitiens . Eight species were collected on Tongatapu Island ( A. horrescens being absent), four species on 'Oneata Island ( A. albopictus, A. horrescens, C. quinquefasciatus and C. annulirostris ), four species on 'Eua Island ( A. aegypti, A. albopictus, A. tongae and C. quinquefasciatus ) and one on Pangaimotu Island ( A. aegypti ). Species collected from 'Eua and 'Oneata islands represent first‐time collections of these species on these islands. Aedes aegypti, A.albopictus and C. quinquefasciatus were the three most common species collected and have markedly increased their distribution since the 2006 survey. The collection of A. albopictus is the second time that this species has been recorded in Tonga; however, the spatial extent of this species throughout Tongatapu was far greater than previously recorded. Management should focus on reducing the number of artificial habitats by covering, emptying or infilling these habitats with soil to minimise mosquito oviposition. This should reduce the abundance of mosquitoes and help prevent disease outbreak in Tonga.